Independensi Aparat Pengawas Intern Pemerintah dalam Menghadapi Korupsi, Kolusi, dan Nepotisme di Provinsi Papua - Situmorang, Charles Pangidoan (Jurnal Administrasi Publik (Public Administration Journal), 2019)
This study aims to show the results of a review of three main domains found in APIP in Papua Province, namely the determinants of independence, the determinants of eradicating corruption, collusion and nepotism, and the determining factors among them. This study is an evaluative qualitative study to assess the conditions of the determinants of independence, eradicating corruption, collusion and nepotism in Papua Province. Data obtained from secondary sources in the form of government reports and mass media and scientific literature. Research cases in this study are government corruption cases in the Papua Province in 2013-2018. For each example, researchers identified the role of APIP and disclosure. The study of literature derives he classification of determinants. This finding is discussed together with several recommendations needed to improve APIP independence and prevention of Community Service in Papua.